Exploring teacher wellbeing in educational reforms: a Chinese perspective - Ao, Narentuya; Zhang, Sitong; Tian, Guoxiu; Zhu, Xiaoshuang; Kang, Xiaowei (Frontiers in Psychology, 2023)
In the paper are not included the instruments used to collect informations so it's quite hard to express an evaluation on this part.Suggested intervenstion 1: insert the questionnaire translated in English.The original Chinse questionnaire was translated into English and was submmiteed as a separate file for further revision.Suggested intervention 2: devote a part of the text to some considerations about well being in general, not only about teachers.A part concerning wellbeing in general was added in the manuscript.In the discussion I suggest that the authors keep in mind the idea that organizational and work changes are stressing in se. I find quite risky to not take in consideration the sistemic condition but only the indidual characteristics, I suggest that at least a paragraph of discussion of this choice will be included.